Social Media and Ubiquitous Technologies for Remote Worker Wellbeing and Productivity in a Post-Pandemic World - Das Swain, Vedant; Saha, Koustuv; D. Abowd, Gregory; De Choudhury, Munmun (2020 IEEE Second International Conference on Cognitive Machine Intelligence (CogMI), 2020)
In light of the ongoing COVID-19 pandemic, remote work styles have become the norm. However, these work settings introduce new intricacies in worker behaviors. The overlap between work and home can disrupt performance. The lack of social interaction can affect motivation. This elicits a need to implement novel methods to evaluate and enhance remote worker functioning. The potential to unobtrusively and automatically assess such workers can be fulfilled by social media and ubiquitous technologies. This paper situates recent research in the new context by extending our insights for increased remote interaction and online presence. We present implications for proactive assessment of remote workers by understanding day-level activities, coordination, role awareness, and organizational culture. Additionally, we discuss the ethics of privacy-preserving deployment, employer surveillance, and digital inequity. This paper aims to inspire pervasive technologies for the new future of work.